ENDOSCOPIC ULTRASOUND CHARACTERISTICS IN THE DIAGNOSIS OF PANCREATIC CYSTIC LESIONS AT THE GASTROENTEROLOGY AND HEPATOLOGY CENTER, BACH MAI HOSPITAL, 2024–2025 (Vietnam Journal of Community Medicine, 2026)
Background and Objective: Pancreatic cystic lesions (PCLs) are increasingly detected due to advances in imaging modalities. Differentiating between neoplastic cysts (IPMN, MCN, SCN, SPPN, etc.) and non-neoplastic cysts is crucial for determining whether surgical resection or surveillance is appropriate. Endoscopic ultrasound (EUS), with its high-frequency transducer and close proximity to the pancreas, allows for accurate evaluation of high-risk features such as mural nodules, cyst wall thickening, and main pancreatic duct (MPD) dilation, thereby elucidating the true nature of the lesion.Objective: To describe the EUS characteristics of pancreatic cystic lesions.Materials and Methods: A cross-sectional descriptive study was conducted on 25 patients with pancreatic cystic lesions at the Gastroenterology and Hepatology Center, Bach Mai Hospital (May 2024 – May 2025). All patients underwent CT/MRI, EUS ± FNA, and had histopathological confirmation. Data were analyzed using SPSS to calculate sensitivity (Se), specificity (Sp), and diagnostic concordance of EUS and MRI compared with histopathology. Results: Female patients accounted for 56%, with the 60–79-year-old group being the most common (48%). The most frequent symptoms were abdominal pain (60%) and diabetes (56%). On EUS, heterogeneous hypoechogenicity (44%) was associated with malignancy in 72.7%, and solid/thick-walled cysts carried a 50% malignancy risk. A strong correlation was observed between mural nodules ≥ 5 mm and malignancy (70%, p = 0.002). Thickened cyst walls > 2 mm on EUS were significantly associated with malignancy (p = 0.005). EUS showed higher sensitivity and specificity (72.9% and 85.1%, respectively) than MRI (61.9% and 63.9%) in identifying the true nature of lesions compared with histopathology. MPD dilation ≥ 10 mm was mainly observed in IPMN cases and strongly correlated with high-grade dysplasia or malignancy. Conclusion: EUS provides superior diagnostic performance compared with MRI in detecting high-risk features of pancreatic cystic lesions—particularly mural nodules, thickened walls, and heterogeneous echogenicity. Combining EUS and MRI improves diagnostic accuracy and optimizes treatment strategies for patients with pancreatic cystic lesions.
Keywords: Endoscopic ultrasound; Pancreatic cyst; Solid nodule; Mural thickness; Histopathology.